FORMULASI SEDIAAN ANTISEPTIK DARI BUAH RIMBANG (Solanum torvum) SEBAGAI HAND SANITIZER - Siti Maimunah; Yettrie Simarmata; Eka Margaret Sinaga; Kristini Siboro (Jurnal Farmanesia, 2018)
Rimbang fruit (Solanum torvum) has properties as a skin antiseptic. Rimbang fruit extract (Solanum torvum) which has been isolated has antibacterial activity against Staphylococcus aureus bacteria. This is because the Rimbang fruit extract (Solanum torvum) contains compounds such as solasonins, glucosides, saponins, and sterolins. Formulation and testing of antibacterial activity of hand sanitizer gel preparations of Rimbang fruit extract and evaluation of the physical quality of hand sanitizer preparations. Rimbang fruit extract was made by the maceration method using 70% ethanol. Then it was evaporated using a rotary evaporator and the remaining solvent was evaporated until a thick extract was formed. Testing of antibacterial activity by agar diffusion method using disc paper against Staphylococcus aureus by measuring the diameter of the zone of inhibition of bacterial growth. The concentration of Rimbang fruit extract and hand sanitizer gel formula used (F1) 0.5% and (F2) 1%; Evaluation of the physical quality of the hand sanitizer preparation includes organoleptic test, homogeneity test, and pH test. The results of the antibacterial activity test of Rimbang fruit extract against Staphylococcus aureus at a concentration of 0.5% with an inhibitory diameter of 5.2 mm. Meanwhile, the results of the gel hand sanitizer activity test of Rimbang fruit extract obtained the inhibition of Staphylococcus aureus bacteria at a concentration of 1% with a diameter of 9.0 mm.